When Imagination Feels Like Reality: A Case Study of False Memories and Maladaptive Daydreaming in Visual Impairment - Eli Somer (Case Reports in Psychiatry)
Background. When a person experiences maladaptive daydreaming (MD), they spend a prolonged period daydreaming with a strong sense of presence. The symptoms of MD are often excessive, interfere with functioning, and are linked to distress and comorbid mental disorders. In this paper, apparent false memory is described in the context of a woman with MD and visual impairment due to a progressive eye condition. Her vivid daydreams seemed indistinguishable from actual memories. Case Report. A 35-year-old woman with a lifelong MD reported three incidents of fabricating detailed false memories of events that her family confirmed never occurred: obtaining a new job, miscarrying twins, and hospitalization for COVID-19. She experienced anxiety and shame when the stories were disproven. The assessment confirmed MD, PTSD, OCD, and other disorders. Her verbal memory was below average, especially for longer narratives. Her misattributions of daydreams as real-life memories may relate to reliance on vivid mental images over deteriorating vision and source monitoring deficits. Conclusion. This first reported case of confabulations in an individual with MD and visual disability suggests daydreams could potentially be mistaken for actual events in some MD cases. While sensitive, more research is needed on the prevalence of false memories among individuals with MD. The default mode network, prefrontal cortex, and their connectivity may be implicated in generating vivid daydreams and misattributing them to actual episodic events. Understanding the relationship between sensory impairments, dissociation, and susceptibility to memory distortions could inform interventions to improve reality testing for some MD patients.